2014
DOI: 10.1137/120901246
|View full text |Cite
|
Sign up to set email alerts
|

Denoising an Image by Denoising Its Curvature Image

Abstract: In this article we argue that when an image is corrupted by additive noise, its curvature image is less affected by it; i.e., the peak signal-to-noise ratio of the curvature image is larger. We speculate that, given a denoising method, we may obtain better results by applying it to the curvature image and then reconstructing from it a clean image, rather than denoising the original image directly. Numerical experiments confirm this for several PDE-based and patch-based denoising algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…In some sense, the denoising process preserves the first order local geometry of the image. Inspired by [3] where it is shown that curvature information is less corrupted than first order local geometry under additive Gaussian noise, we are currently investigating projections taking into the curvature information of Riemannian manifold. Finally, we would like to point out that the step 2 of our denoising method might be extended to any denoising method.…”
Section: Resultsmentioning
confidence: 99%
“…In some sense, the denoising process preserves the first order local geometry of the image. Inspired by [3] where it is shown that curvature information is less corrupted than first order local geometry under additive Gaussian noise, we are currently investigating projections taking into the curvature information of Riemannian manifold. Finally, we would like to point out that the step 2 of our denoising method might be extended to any denoising method.…”
Section: Resultsmentioning
confidence: 99%
“…Such an approach motivated the Bregman iterations-based denoising algorithm of Osher et al [26], [36]. More recently, Bertalmío and Levine [9] adopted a similar approach but dealing with the curvature of the level-lines.…”
Section: A Short Overview On Variational Methods For Image Regularizamentioning
confidence: 99%
“…Dealing with grey-level images, we compare our method with three variational denoising methods whose fidelity term, like our method, is not spatially adapted, namely the curvature-based denoising method of Bertalmío and Levine applied to the ROF model [9], Bregman iterations [36], and Chambolle's algorithm [14]. We also compare with the method of Gilboa et al [23] that does contain a spatially adapted fidelity term dedicated to take into account the texture information of the image.…”
Section: 52mentioning
confidence: 99%
See 2 more Smart Citations